Kierunek – Nowa Huta! . Destination Nowa Huta! - Munk, Andrzej (Poland, 1951)
Verzio FF Andrzej Munk’s first short documentaries evolved from social realist pieces to personal artistic statements, captivatingly combining lyricism and satire. This film is a model propaganda poster of the Polish cinema of the Stalinist era, glorifying the giant construction of the steel works and town of Nowa Huta. The treatment of the workers is self-consciously “heroicizing,” emphasizing muscled bodies against the skyline.